Hasil Problem Based Learning (PBL) Analisis SWOT Dengan Olahan Susu Di Cafe Milk Square - Sandya Pramunitia; M.Abdul Azim; Visalwa Enggela; Isra Maulina; Dinal Adriansyah; Ramdani Bayu Putra (Jurnal Masyarakat Mengabdi Nusantara, 2023)
The processed milk used usually comes from dairy cows which are very efficient at converting fodder in the form of concentrates and forages into milk which is of great benefit to human health. In recent years, the development of cafe milk made from dairy cow's milk in Indonesia has developed rapidly. But of course it raises problems related to competition. The way to win the competition is that restaurants must try to find out what consumers need and want, so that consumers decide to buy their products. So a SWOT analysis is needed, namely Strength, Weakness, Opportunity, and Threat that is right in facing the competition in the business world. So that the company gets a big advantage by knowing the SWOT analysis of its marketing strategy.